Zapping Zone and Level Five. Between the visitor’s experience of the video installation and the filmmaker’s reflection of the essay film - Monterrubio-Ibáñez, Lourdes (Arte, Individuo y Sociedad, 2023)
The displacement from the essay film to the video installation has in Chris Marker one of its first and most relevant figures. The comparative study of Zapping Zone. Proposal for an imaginary television (1990) and Level Five (1997) allows for the analysis of the construction and complexification, and the deconstruction and saturation processes that take place between the most complex expression of the Markerian essay film and its transformation into the video installation. Zapping Zone responds to the embodiment of both the magmatic stage of the postmodern audiovisual era and the starting point of the filmmaker’s work (documentaries, essay films, video installations, etc.), which would be the opposite of the writer’s blank page: a saturated world of images that needs to be selected, analysed and worked on in order to build meaning. Level Five offers the filmmaker’s reflection on that same reality, applied to the Battle of Okinawa, through a complex audiovisual thinking process that hybridises different types of images—documentary and fictional; analogue and electronic—devices—epistolary video diary, video game and cyberspace—and their authorial subjectivities—Laura, Laura’s lover and Chris—in order to reflect on the relationship between these audiovisual forms and spaces and the thematic axis memory-pain-oblivion.